Failure mechanism of prepacked concrete - Abdul Awal, A. S. M. (American Society of Civil Engineers, 1988)
Concrete is a multiphase material in which aggregate particles are distributed in the mortar matrix. Since a large volume of the concrete is occupied by aggregate, it is likely that variation in aggregate content will significantly influence the strength and deformation behavior. Prepacked concrete, as it contains a higher proportion of coarse aggregate, shows characteristics in failure that are widely dissimilar from those of normal concrete. This paper presents some aspects of failure mechanism of prepacked concrete observed during testing in compression. Along with the observations, some theoretical considerations are also made and discussed.